A Blueprint for Digital Climate-Informed Advisory Services: Building the Resilience of 300 Million Small-Scale Producers by 2030 - Ferdinand, Tyler; Illick-Frank, Emma; Postema, Louise; Stephenson, Jim; Rose, Alison; Petrovic, Darko; Migisha, Claude K.; Fara, Katiuscia; Zebiak, Stephen E.; Siantonas, Tony; Pavese, Nicoletta; Chellew, Tom; et al. (World Resources Institute, 2021)
In 2019, nearly 750 million people faced food insecurity, with that number expected to increase in the coming years. Climate change could significantly depress global crop yields, but adaptation efforts could help decrease this risk. The Blueprint for Digital Climate-Informed Advisory Services lays the conceptual foundation for building the climate resilience of at least 300 million small-scale agricultural producers by 2030.